The gifted child: psychological-pedagogical aspect of future teacher's training - Halyna Boryn (Vasyl Stefanyk Precarpathian National University, 2017)
The applied aspect of interdisciplinary integration in professional training of future teachers of preschool educational institutions to work with artistically gifted children by integrating the content of the normative educational disciplinesis outlined inthe article. It is  52 focused on combining the new and known methods of students'educational activity by transferring knowledge and skills to new situations on the basis of subject-subjective interaction; it is identified psychological and pedagogical aspects of training of future preschool educators to work with gifted children in the conditions of higher educational institution. Key words: professional training of students, the integration of the content of normative educational disciplines, artistic-aestheticdevelopment, artistic talent.